Judicial Review as an Instrument for Protecting Hifz Al-Din and Hifz Al-Nafs in a Pancasila-Based Constitutional State - Mawardi (Universitas Muhammadiyah Palu, 2026)
Judicial review constitutes a fundamental legal mechanism within the Pancasila-based rule of law, particularly in safeguarding constitutional supremacy and protecting the fundamental rights of citizens. Through judicial review, the state ensures that legislative and regulatory frameworks remain consistent with the 1945 Constitution of the Republic of Indonesia as well as the foundational values of Pancasila. In this regard, judicial review functions not merely as a formal process of legal norm assessment, but also as a substantive instrument for preserving humanitarian and moral values aligned with the concept of maq??id al-shar?‘ah, especially ?if? al-d?n (protection of religious freedom) and ?if? al-nafs (protection of human life). This article aims to examine the role of judicial review as a mechanism for safeguarding freedom of religion and the right to life within the framework of Indonesia’s Pancasila-based legal system. The analysis focuses on how the Constitutional Court, through its authority to review legislation, contributes to maintaining a balance between state interests, constitutional principles, and human rights protection. The research employs a normative juridical approach by analyzing statutory regulations, Constitutional Court decisions, and relevant legal literature from both positive law perspectives and maq??id al-shar?‘ah theory. The findings indicate that judicial review holds significant relevance in advancing the protection of ?if? al-d?n and ?if? al-nafs, as it enables the correction of legal norms that potentially threaten religious freedom and the preservation of human life. Therefore, judicial review serves not only as a formal constitutional instrument but also as a substantive means of upholding justice, human dignity, and Pancasila values within the national legal system.